ESTUDOS ESPECTROSCÓPICOS DE PORFIRINAS COMPLEXADAS COM Cu²+ - Gonçalves, Joyce Laura da Silva (2011)
Porphyrins are very interesting because their favorables characteristics on biomedical applications. Paramagnetic metalloporphyrins have been studied and were exhibited promising results as contrast agents in nuclear magnetic resonance imaging. In aqueous medium, these compounds have the ability to form aggregates that minimize their effectiveness for therapeutic purposes. Therefore, the investigation of properties of porphyrin in the presence of biological systems model can support a better understanding of the interaction of porphyrins with tissues in the blood. In the present study we used spectroscopic techniques, to investigated the influence of pH, ionic strength in the two porphyrins complexed with Cu²+: meso-tetrakis (N-methyl-4-pyridyl),CuTMPyP and meso-tetrakis(2-bipyridinil-2-chlorine--ruthenium)CuTPyP{Ru(bipy)2Cl}4, and their interaction with biological model systems. As model systems we used the cationic surfactant cetyltrimethylammonium bromide (CTAB), the nonionic polyoxyethylene stearyl ether (20) (Brij 78) and anionic sodium dodecyl sulfate (SDS) in micellar form. The optical absorption showed that the CuTMPyP was insensitive in the pH range of 0,5 to 13,0 and only one specie was observed. This porphyrin were not influenced by ionic strength. No significant interaction of porphyrin with micelles of CTAB and Brij 78 were occurred. However, in the presence of SDS an effective interaction of porphyrin and SDS was observed. Optical spectra reveal a decrease of de Soret band at 425 nm with increasing SDS concentration until 3,12 x10 -4 mol L?¹. Over this range there is a small red shift in the Soret band and its absorbance increasing with SDS concentration. In conclusion, due to preferential interaction with anionic micelles, the electrostatic factor seems to be more relevant. This result was confirmed by EPR and MCD results. A superhyperfine structure corresponds to four equally coupled nitrogens, i.e., nine lines pattern was observed. Then in the used pH range there is neither change in the binding of Cu in the porphyrin ring nor axial ligands exchanges. The value of g0?2,075 was calculated. Three distinct species in solution equilibrium to the optical absorption spectrum for CuTPyP{Ru(bipy)2Cl}4 were showed. The pK1=3,5± 0,5 and pK2=10,6± 0,6, whose forms are diprotonated, monoprotonated and no protonated were reported. In this case, the ionic strength above 5,9x10-1 mol.L?¹ were denoted. No significant interaction of porphyrin with micelles of CTAB and Brij 78 were occurred again. However, there was a high interaction with anionic surfactant. A decrease of de Soret band at 417 nm with increasing SDS concentration until 5,1x10-4 mol.L?¹ were observed. Thereafter, a small red shift in the Soret band and its absorbance increasing with SDS concentration were observed. One more time, the electrostatic factor was very relevant. The MCD and EPR were in agreement with this results. The hyperfine structure resulted from the interaction between delocalized ? electron and N magnetic nuclei was just observed in presence of SDS micelles. EPR data at 77 K presented a typical axial spectrum with g//?2.345 and g??2.026 for all situations. Due to high concentration of both porphyrins used, only free form of porphyrin and theirself interaction of SDS micelles were observed in MCD and EPR spectra. M oreover, the electrostatic factor proved to be the most important factor in interactions of porphyrins.